2015
DOI: 10.1080/08927022.2015.1048511
|View full text |Cite
|
Sign up to set email alerts
|

Computational exploration of metal–organic frameworks: examples of advances in crystal structure predictions and electronic structure tuning

Abstract: Special Issue : Molecular simulation of framework materialsInternational audienceThe purpose of this article is to consider some recent developments in the area of the computational chemistry of metal–organic frameworks (MOFs), and more specifically on their crystal structure prediction and electronic structures. We intend here to illustrate how computational approaches might be powerful tool for the discovery of new families of hybrid frameworks, helping to understand their often complex energy landscapes. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…This wavelength range that caused photo-accelerated decomposition of ZIF-8 in water is rather unexpected. This is because theoretical calculations and experimental results , (also Figure S2) showed that the bandgap energy of ZIF-8 is between 4.8 and 5.5 eV. ZIF-8 should be inactive to the light with an energy lower than the bandgap energy.…”
mentioning
confidence: 94%
“…This wavelength range that caused photo-accelerated decomposition of ZIF-8 in water is rather unexpected. This is because theoretical calculations and experimental results , (also Figure S2) showed that the bandgap energy of ZIF-8 is between 4.8 and 5.5 eV. ZIF-8 should be inactive to the light with an energy lower than the bandgap energy.…”
mentioning
confidence: 94%
“…The concept of crystal design came to crystal chemistry recently but immediately led to rapid development of structural chemistry of different classes of substances with extended architectures such as coordination polymers of different periodicities (chain one-dimensional, layered two-dimensional, or framework three-dimensional). This concept gained its theoretical basis from “reticular” chemistry, which is in turn based on the topological (graph) approach . Thus, topological properties of crystal structures became important and resulted in successful synthesis of large families of isoreticular metal–organic frameworks (MOFs). , It is the topological methods that enabled one to reveal many correlations of “chemical composition – structure – property”, which were then used in crystal design. , The main route of reticular chemistry in obtaining new coordination polymers includes utilizing structural units with predetermined topology and geometry (secondary building units, SBUs) for decoration of a particular topological motif (periodic net). Importantly, this approach can be readily algorithmized and implemented into computer tools for analysis of crystal structures, their topological classification, and design of new crystalline compounds. However, complicated compounds consisting of SBUs with a high degree of freedom and extended connection possibilities are still a challenge for crystal design. This promoted inventing new structural descriptors and models that could reliably discriminate different topological motifs at both local and overall level, such as coordination figure, ligand coordination type symbol, Hopf ring net, , net topological indices and tilings . These were formalized, digitalized, and computed for thousands of crystal structures from crystallographic databases such as the Cambridge Structural Database (CSD), Inorganic Crystal Structure Database (ICSD), or Pearson’s Crystal Database .…”
Section: Introductionmentioning
confidence: 99%
“…Two well-known comments on the situation are “A continuing scandal in physical sciences” by J. Maddox in the editorial of Nature in 1988, and “Are crystal structures [at all] predictable?” by J. Dunitz in 2003. Since then, the ab initio, semiempirical, genetic/evolutionary algorithms, and, importantly, stochastic (Monte Carlo) CSP methods made very significant progress with a variety of methods/software available today. However, they do not provide a final solution, being computation-hungry and easily missing local minima, which correspond to the actually existing polymorphs. It is particularly true when the nonbonding dispersive (van der Waals) interactions represent a significant part of the total formation energy share.…”
Section: Introductionmentioning
confidence: 99%